PP55 Socioeconomic Status and Chronic Kidney Disease: Further Findings from the Health Surveys for England 2009 and 2010. (10th September 2013) - Fraser, S D S; Roderick, P J; Aitken, G R; Roth, M A; Mindell, J S; Moon, G; Matthews, B; O'Donoghue, D J
Abstract : Background: Renal replacement therapy rates are higher in more deprived populations in developed countries. The relationship between population-level prevalence of chronic kidney disease (CKD) and socio-economic status (SES) is less clear. Albuminuria is also recognised as an independent risk factor for poor CKD outcomes but again little is known about its relationship with SES. The nationally representative Health Surveys for England (HSE) 2009 and 2010 showed mixed evidence for variation of CKD prevalence by area deprivation defined by 'Spearhead Primary Care Trust' status. The present study aimed to examine the relationship between CKD and SES in more detail, and to include investigation of associations of albuminuria. Methods: Data from the 2009 and 2010 HSEs were combined, giving a total of 5, 799 individuals with kidney function data. Prevalence of moderate to severe CKD (stage 3–5), using the Chronic Kidney Disease Epidemiology Collaboration (CKDEPI) estimating equation, and albuminuria were calculated. Multivariate logistic regression models were used to determine the associations of SES measures with CKD and albuminuria, adjusted for demographic, lifestyle and clinical factors. Results: Prevalence of CKD Stage 3–5 was 5.2%, and any albuminuria 8.0%. After accounting for age-sex interaction, age-sex adjusted CKD 3–5 prevalence was associated with lack of qualifications (OR 2.27 [95% CI 1.40, 3.69]), low income (1.50 [1.02, 2.21]) and household tenure (1.36 [1.01, 1.84]) for rented vs. ownership). Only tenure remained significant after further adjustment for lifestyle and clinical factors (smoking, body mass index, hypertension, diabetes and ethnicity). Age-sex adjusted albuminuria prevalence was associated with low income (1.79 [1.35, 2.36]) most deprived quintile of index of multiple deprivation (1.72 [1.24, 2.41]), vehicle ownership (1.59 [1.25, 2.02]) and tenure (1.46 [1.18, 1.81]); these associations persisted after full adjustment. Conclusion: There was little evidence of socioeconomic variation in CKD 3-5 prevalence in these HSE participants. By contrast, albuminuria prevalence varied by several measures of SES. This suggests a higher risk of CKD progression in lower SES groups. When combined with the higher prevalence of Type 2 diabetes in lower socioeconomic groups, this may contribute to the inverse gradient of renal replacement therapy rates by SES. This has implications for the early detection of CKD and albuminuria, and for equity of care in managing CKD.